Management of Al-Qur’an Learning Strategies Ummi Method in Children 5-6 Years (Case Study at The Qur’an Training Center Al-Mady Yogyakarta) - Nurfadlilah, Wuri Annisa; Nurhayati, Puput (Proceeding International Conference on Religion, Science and Education, 2025)
The Indonesian state, which has a majority Muslim population, turns out to have a fairly high case of inability to read the Qur’an properly. As the next generation of the nation, children should be prepared to learn the Qur’an well in accordance with the guidance of the Prophet Muhammad SAW, besides that schools should provide adequate and adequate facilities for children in the process of learning the Qur’an. The purpose of the study was to examine the application of the Ummi method in shaping the Qur’ani generation of children aged 5-6 years at the Qur’an Training Center Al-Mady Yogyakarta. This study uses a type of qualitative research with a field study approach. The data collection technique uses observation, interview and documentation techniques. The data analysis technique of the research results shows that the application of the Ummi method in forming the Qur’ani generation systematically is carried out through three stages, namely preparation, application and evaluation. The Ummi method at the Qur’an Training Center Al-Mady Yogyakarta is very effective, systematic and recommended.